The Extraction and Nano Particles Production of Moringa Leaf Bioactive Compounds and Their Identification - Feronyanti Mitranistin Pello; Donn Richard Ricky (Universitas Teuku Umar, 2023)
Moringa leaves (Moringa oleifera) is a vegetable plant from the Brassica order and belongs to the Moringaceae family, known as the “Magic Plant” which has a wide variety of protein content contained in it. Therefore, the bioactive compounds used are Moringa leaves (Moringa oleifera) which have such great potential that they can be developed as raw materials for medicine. However, because the secondary metabolite compounds contained by plants have hydrophobic properties. This property can be one of the obstacles for these secondary metabolites to be easily absorbed by the body because of their nature which is difficult to dissolve in body fluids so that they can be easily degraded by the body's enzymatic system, to overcome this problem Nanoparticles can be a solution in overcoming this problem. the manufacture of nanoparticles has been carried out. To produce nanoparticles of Moringa leaf bioactive compounds, synthesized using tween 80 surfactants, has been carried out using the spontaneous emulsion method. The bioactive compounds contained in Moringa leaves (Moringa oleifera) are: (1) 9-Octadecenoic acid (29.64%), (2) Hexadecanoic acid (18.42%), (3) Octadecanoic acid (7.07%), (4) Oleic Acid (5.88%), and (5) 14-Methyl-8-hexadesin-1-ol (5.47%). Synthesis using four different concentrate masses of these compounds, namely: 2 mg, 1.5 mg, 1 mg and 0.5 mg dissolved in 100 ml of ethanol, resulted in an average diameter of each nanoparticle of 15.9 nm; 15.5nm; 14.7nm; and 14.8 nm. The polydispersity index is 0.306; 0.258; 0.122; and 0.282. From the results above, it has been shown that the process of synthesizing nanoparticles of secondary metabolites of ethanol extract using the spontaneous emulsion method has produced small-sized particles. This allows the development of site results to be used in applications in various fields such as in the pharmaceutical field in the drug development process.